Bombo’s Ritual Journey: An Overview of Tamang Worldview and Aesthetics - Lama, Kumari (Mindscape: A Journal of English & Cultural Studies, 2024)
Indigenous Tamang community adopts unique methods to deal with certain ailments that trouble either an individual, livestock or the whole village. Primarily, they seek help from a traditional healer and ritual practitioner such as Bombo to get rid of their problems. The ritual specialist invokes the trouble creating agents and pacify them through proper ritual performances and sacrificial offerings. During the process, Bombo takes rirap, a ritual journey along with the recitation of special verses. Bombo, in his internal/ psychological journey, reaches several places, addresses the powerful god and goddess through chanting and at the end returns back to his own locality. Against the backdrop of Tamang ritual practices, this paper analyzes Bombo’s verses that they recite during Piksu mang (spirit/bhut) and Syibda-neda (sime-bhume) rituals to identify certain features that substantiate Tamang worldview and aesthetics. For this purpose, I have used selected texts from András Höfer’s Tamang Ritual Texts I: Preliminary Studies in the Folk-Religion of an Ethnic Minority in Nepal (1981) and Tamang Ritual Texts II: Ethnographic Studies in the oral Tradition and Folk-Religion of an Ethnic Minority in Nepal (1997) as primary texts. I have incorporated the ideas of Richard Schechner (2003) and David H. Holmberg (2005) about rituals for theoretical backing. Mainly, this paper concentrates on the analysis of Bombo’s recitations and observes how those ritual recitations ratify Tamang worldview and aesthetics.